Body as Membrane. - Ahtila, Eija-Liisa; Burkard, Lene; Eiblmayr, Silvia; Elovirta, Arja; Export, Valie; Jonas, Joan; Justesen, Kirsten; Knudsen, Anne; Ll, Natalia; Obrist, Hans-Ulrich; Ohrt, Karsten; Ruhs, August; et al. (Odense : Kunsthalle Brandts Klaedefabrik, 1996)
Ahtila, Eija-Liisa ; Cox, Renée ; Export, Valie ; Jonas, Joan ; Justesen, Kirsten ; Kelly, Mary ; Knowles, Alison ; Krystufek, Elke ; LL, Natalia ; Orlan ; Parker, Jayne ; Rekula, Heli ; Schneemann, Carolee ; Sprinkle, Annie ; Mendieta, Ana ; Pane, Gina ; Wilke, Hannah
biografie
Body as Membrane, Kunsthalle Brandts Klaedefabrik, Odense, 12. Januar - 17. Marts 1996
Deens & Engels
boek